Avaliação da assistência pré-natal de mulheres com síndrome hipertensiva gestacional - Herculano, Marta Maria Soares (2010)
This study aimed to evaluate prenatal care given to women with Gestational Hypertensive Syndrome. This is a descriptive, transversal and evaluation study with quantitative approach, held in the Maternity School Assis Chateaubriand (MEAC) in Fortaleza. The sample consisted of 230 women admitted at the maternity, diagnosed with Gestational Hypertensive Syndrome (GHS). The data was collected from March to November 2010, using a structured form and examination of the patients’ medical records. Most women, 134 (58.3%), were between the age of 20-34years, being the majority (65.7%) from the capital. 126 (54.8%) of the 230 women were young first-time mothers and 37 (16.1%) had a prior history of preeclampsia. 230 medical records were individually analyzed. From this it was found that 194 pregnant women were admitted with preeclampsia corresponding to 88.8%. However severe preeclampsia was the higher prevalence with 57.0% of admissions. Regarding risk factors, the main factor associated with SHG was prior preeclampsia with 37 (16.1%) cases, followed by HAC with 34 (14.8%). Among the key signs and symptoms at the time of admission were: increased High blood pressure totaling 200 women, with an average Systolic blood pressure of 164.2 with DP of 22.4, followed by proteinuria (148), and headache (127). The gestational age ranged from 18 to 42 weeks, with an average of 36.4, with a DP of 3.82. Caesarean was the prevalent choice of childbirth (77.4%). Regarding the pre natal data, 147 (63.91%) women began their appointments in the first trimester, 121 (48.5%) attended from 6 to 13 appointments with an average of 5.9 and DP of 2.2. 128 of these women were accompanied by two professionals: a doctor and a nurse. All laboratory tests and procedures recommended by PHPN were noted, over 80%, excepting the second samples of the following tests: VDRL, urine, HIV and blood glucose. Therefore, not fulfilling what is established by PHPN, in other words, the running of the second sample around the 30th week of gestation. In conclusion, this study has its relevance by reinforcing the route of prenatal assistance until the outcome in the attendance at the hospital. It shows us the factors related to prenatal follow-up, reaffirming that the mere realization does not ensure the minimization of the emergence of GHS, being fundamental the qualitative investment of this action